Disraeli and the Eastern Question - Kovic, Milos (Oxford University Press, 2010)
The first full reconstruction of Disraeli's attitudes towards the east and the eastern question as a whole, from his early youth onwards, using a wide array of primary sources, from his own private papers through to contemporaneous Russian, Serbian and Albanian documents.